Higher Education Employees’ Workplace Learning Within Three Schemes of International Mobility - Rojek, Marcin; Leek, Joanna (International Journal of Research in E-learning, 2021)
Studies on the educational dimension of international mobility discuss the implications of academic, international mobility in general, or focus mainly on students’ mobility. There is, however, an insufficient number of studies that focus on the mobility of higher education staff, particularly in relation to learning. Each year, studies on the impact of mobility are published by the European Commission, but this does not provide an overview of how adult learning occurs within mobility and how mobility affects the lifelong learning of higher education employees. The purpose of this paper is to describe and explain HE employees’ learning characteristics in the course of three types of mobility: traditional, blended and digital. The study was conducted with the participation of 103 staff members of European Universities from 17 countries. We claim that the three mobility schemes studied here are different ways of experiencing the world and learning. Therefore, they should be implemented in parallel, and not perceived as alternatives.